2022
DOI: 10.1021/acs.jpca.2c04265
|View full text |Cite
|
Sign up to set email alerts
|

NO (A) Rotational State Distributions from Photodissociation of the N2-NO Complex

Abstract: We have recorded the resonance-enhanced multiphoton ionization spectrum for NO (A) products from photodissociation of the N2-NO complex. We made measurements at excitation energies ranging from 28 to 758 cm–1 above the threshold to produce NO (A) + N2 (X) products, and the resulting spectra reveal the NO (A) rotational states formed during dissociation, allowing us to determine the rotational state distribution. At the lowest available energies, 28 and 50 cm–1 above threshold, we observed contributions from NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Here the distribution falls to a minimum at N = 5, with weak minima also indicated at N = 0 and 8. This is similar to the behavior seen for NO–Ar ,, and quite different to that recently reported for NO–N 2 [ref ] (see also section ).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Here the distribution falls to a minimum at N = 5, with weak minima also indicated at N = 0 and 8. This is similar to the behavior seen for NO–Ar ,, and quite different to that recently reported for NO–N 2 [ref ] (see also section ).…”
Section: Resultssupporting
confidence: 82%
“…The distributions are quite simple, with maxima at low N (0 and 1 for 44,375 and 44,475 cm –1 photolysis, respectively) with a monotonic decay to higher N . Very recently, Parsons et al have reported similarly shaped distributions for E a from 28 to 758 cm –1 . These authors reported average NO rotational energies at a range of available energies with which our values can be compared.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations